Neurohormonal Regulation of the Hair Cycles in Rats and Mice - Houssay, Alberto B.; Epper, Carlos E.; Pazo, Jorge H. (Angus and Robertson; Australia, 1965)
Fil: Epper, Carlos E. Comisión Nacional de Energía Atómica; Argentina